2017
DOI: 10.3945/jn.117.255356
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Iron-Biofortified Beans Positively Affects Cognitive Performance in 18- to 27-Year-Old Rwandan Female College Students in an 18-Week Randomized Controlled Efficacy Trial

Abstract: Background: Evidence shows that iron deficiency in adulthood may affect cognitive performance, possibly by disrupting neurotransmitter regulation or brain energy metabolism. Women of reproductive age (WRA) are among those who are most vulnerable to iron deficiency; however, they have been largely ignored in the literature relating iron status to cognition.Objective: Our aim was to determine the efficacy of iron-biofortified beans in improving cognition in WRA compared with control beans.Methods: A double-blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 41 publications
2
49
0
2
Order By: Relevance
“…Common bean (Phaseolus vulgaris L.) is the most essential grain legume for human diets, particularly in eastern and southern Africa as well as Latin America where it is a major staple food (Broughton et al, 2003;Petry et al, 2015). It is principally important as a major source of protein and micronutrients for resource disadvantaged smallholder farmers in eastern, southern and parts of central Africa (Murray-Kolb et al, 2017;Petry et al, 2015). Because of this, bean breeding programs in sub-Saharan Africa have directed efforts to develop and release new varieties for enhanced production and nutritional value that are adapted to target agro-ecologies and resilient to climate change (Blair et al, 2010a;Buruchara et al, 2011;Kamfwa et al, 2015;Kimani et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Common bean (Phaseolus vulgaris L.) is the most essential grain legume for human diets, particularly in eastern and southern Africa as well as Latin America where it is a major staple food (Broughton et al, 2003;Petry et al, 2015). It is principally important as a major source of protein and micronutrients for resource disadvantaged smallholder farmers in eastern, southern and parts of central Africa (Murray-Kolb et al, 2017;Petry et al, 2015). Because of this, bean breeding programs in sub-Saharan Africa have directed efforts to develop and release new varieties for enhanced production and nutritional value that are adapted to target agro-ecologies and resilient to climate change (Blair et al, 2010a;Buruchara et al, 2011;Kamfwa et al, 2015;Kimani et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A recent randomized controlled trial among Rwandan women demonstrated significantly improved iron statuses after consuming biofortified iron beans as part of a plant‐based diet for duration of 128 days, supporting the efficacy of the intervention (Haas et al., ). In addition, improved cognitive performance was demonstrated in the women who had consumed biofortified iron beans (Murray‐Kolb et al., ). These women, however, consumed 300–350 g beans daily under ideal feeding conditions, while the majority of our population eats beans on a weekly basis.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive performance was measured in a subsection of the women ( n = 150), using five measures of functioning thought to be dependent on iron status (Murray‐Kolb et al . ). Baseline measures did not differ between the two groups.…”
Section: Ironmentioning
confidence: 97%
“…) and one study suggests improvements in cognitive performance (Murray‐Kolb et al . ). Interestingly, a meta‐analysis including three studies (measuring the efficacy of iron rice in the Philippines after 9 months, iron pearl millet in India after 6 months, and iron beans in Rwanda after 4.5 months) found that, overall, iron‐biofortified crops significantly increased serum ferritin (by 1.1 μg/l) and total body iron (by 0.43 mg/kg) but there were no significant effects on haemoglobin, compared with standard crops (Finkelstein et al .…”
Section: Ironmentioning
confidence: 97%